Disjuncts and Conjuncts: A Syntactic Type of Study to Evaluate Kurdish Students' Writing in English (At University Level) - Abbas Jassim Abbas; Jwan Iqbal Mirza (College of Education for Women, 2019)
The principal concern of this study is Disjunct and Conjunct adverbials in the English language. The study sets out to explore and clarify the types, nature and structure of disjuncts and conjuncts. It also aims at testing student's performance to evaluate the use and usage of the disjuncts and conjuncts in their written performance. Two tests, accordingly, were given to some fifty students of at the Dept. of English, at the college of languages (third and fourth stages) in the University of Sulaimani. The hypothesis that the study was based on are those students use disjuncts and conjuncts hardly enough in their writings and when doing so, they generally tend to stick only to the most commonly used and familiar ones to them. The ultimate findings of the study show that this hypothesis is proved.